2022
DOI: 10.3389/fnins.2022.856808
|View full text |Cite
|
Sign up to set email alerts
|

Alternations and Applications of the Structural and Functional Connectome in Gliomas: A Mini-Review

Abstract: In the central nervous system, gliomas are the most common, but complex primary tumors. Genome-based molecular and clinical studies have revealed different classifications and subtypes of gliomas. Neuroradiological approaches have non-invasively provided a macroscopic view for surgical resection and therapeutic effects. The connectome is a structural map of a physical object, the brain, which raises issues of spatial scale and definition, and it is calculated through diffusion magnetic resonance imaging (MRI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 145 publications
(149 reference statements)
0
6
0
Order By: Relevance
“…Preclinical studies in animal models have shown evidence of tumor-induced changes in resting brain connectivity, as well as intra-tumor connectivity changes in reference to tumor volume and angiogenesis using BOLD RS-fMRI [ 81 ]. Additionally, in vivo studies on brain network disruption and alterations in anatomical dysconnectivity (or connectomes) in patients with brain tumors of glial cell origin have contributed to advancing our knowledge of the complex nature of the structural–functional coupling of brain tumors [ 82 , 83 ]. Although still under investigation, multiple studies to date have demonstrated the concordance of RS-fMRI with task-based fMRI or intraoperative mapping, substantiating its clinical utility [ 69 , 80 , 84 , 85 , 86 , 87 , 88 ].…”
Section: Mri Techniquesmentioning
confidence: 99%
“…Preclinical studies in animal models have shown evidence of tumor-induced changes in resting brain connectivity, as well as intra-tumor connectivity changes in reference to tumor volume and angiogenesis using BOLD RS-fMRI [ 81 ]. Additionally, in vivo studies on brain network disruption and alterations in anatomical dysconnectivity (or connectomes) in patients with brain tumors of glial cell origin have contributed to advancing our knowledge of the complex nature of the structural–functional coupling of brain tumors [ 82 , 83 ]. Although still under investigation, multiple studies to date have demonstrated the concordance of RS-fMRI with task-based fMRI or intraoperative mapping, substantiating its clinical utility [ 69 , 80 , 84 , 85 , 86 , 87 , 88 ].…”
Section: Mri Techniquesmentioning
confidence: 99%
“… 33 , 34 For instance, gliomas can directly damage white matter tracts and indirectly affect functional network organization. 35 Additionally, gliomas can cause increased or decreased functional connectivity depending on tumor location and characteristics. 36 , 37 These findings underscore the complex interplay between brain tumors and the brain’s intrinsic functional networks.…”
Section: Discussionmentioning
confidence: 99%
“…Second, normative connectome can enhance surgical precision and hence improve treatment outcome of different neurosurgical procedures. For instance, for glioma patients who plan for resection surgery, the application of normative connectome can help in the identification of eloquent areas and motor tracts before operation, hence reducing the number of intra-operative stimulations required to safely confirm a tract, decreasing the likelihood of disruptive seizures, lowering the risks of postoperative neurological deficits, facilitating the resection, and making patients more comfortable during the operation [51,52]. Epilepsy surgery is another example.…”
Section: Applications Of Normative Connectome (Including Dbs)mentioning
confidence: 99%